Uncertainty and non-linear macroeconomic effects of fiscal policy in the US: A SEIVAR-based analysis - Pascal Goemans; Ansgar Belke (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We investigate whether the macroeconomic effects of government spending shocks vary with the level of uncertainty. Using postwar US data and a Self-Exciting Interacted VAR (SEIVAR) model, we find that fiscal spending has positive output effects in tranquil times but is contractionary during uncertain times. The endogenous reaction of macroeconomic uncertainty and consumer confidence play an important role in explaining the non-linear impact of government spending. In contrast to other types of government spending, research and development expenditures reduce uncertainty and have an expansionary effect on output during uncertain times.
Keywords: E62; E32; C32; 330; government spending shocks; uncertainty; non-linear structural vector autoregressions; interacted VAR; generalized impulse response functions; endogenous uncertainty